Readiness and Relationships Are Crucial for Coalitions and Collaboratives: Concepts and Evaluation Tools. Issue 165 (18th March 2020) - Hajjar, Lauren; Cook, Brittany S.; Domlyn, Ariel; Ray, Kassy Alia; Laird, David; Wandersman, Abraham
Abstract: Collaboration is identified as an essential component for the successful implementation of a wide range of policies and programs. A major collaboration challenge, particularly in large community initiatives, is the need for multiple organizations to develop strategic partnerships around a shared purpose. Due to the importance of collaboration in achieving desired outcomes, the readiness of organizations to collaborate, and the quality of relationships between organizations are key, particularly in the formation stage. This is especially true of community coalitions, where collaboration requires comprehensive planning, shared decision‐making among stakeholders, and a high level of productivity and quality of relationships based on trust and mutual respect. In this chapter, we present two evidence‐based frameworks and evaluation tools that can be used to assess and build readiness and high‐quality relationships in efforts to improve community outcomes. This is illustrated in a case example of a new community coalition focused on increasing youth safety and improving police‐community relationships in a high crime neighborhood. Implications and lessons learned are discussed.